Evaluasi perencanaan anggaran dan kompetensi sumber daya manusia terhadap penyerapan anggaran dengan komitmen manajemen sebagai pemoderasi pada satuan kerja kementerian agama Republik Indonesia di Kota Jambi - Rahmawati, Rahmawati; Amir, Amri; Junaidi, Junaidi (Jurnal Paradigma Ekonomika, 2021)
This study aims to analyze budget planning and human resource competence on budget absorption, directly or through management commitment, as a moderating variable in the Indonesian Ministry of Religion Work Unit in Jambi City. This study uses a quantitative approach. Data was collected through a survey using a questionnaire. Data were analyzed using multiple regression analysis (multiple regression) and moderated regression analysis (MRA). The results showed that budget planning and human resource competence simultaneously significantly affected Budget Absorption. There is a positive influence of budget planning factors and human resource competence on budget absorption. Management commitment moderates the influence between budget planning and human resource competence on budget absorption Â